IMPLEMENTASI METODE MICROSERVICE UNTUK PENGEMBANGAN SISTEM INFORMASI KARYAWAN BERBASIS WEB - Nazwa Hanifah; Rahma Santika; Yusuf Maulana; Saprudin (Journal of Research and Publication Innovation, 2025)
This study discusses the implementation of the microservice method for the development of a webbased employee information system at the Meteorology, Climatology, and Geophysics Agency (BMKG). In the current digital era, organizations are striving to improve operational efficiency and effectiveness through information technology, with microservices architecture offering a modular and flexible approach. The main objective of this project is to design and implement a system that streamlines employee attendance and leave application processes, integrating these features into independent yet interconnected microservices. The system utilizes Next.js for the frontend and FastAPI for the backend, ensuring responsive access, real-time data management, and enhanced security. The research methodology includes needs analysis, system architecture design, system development, and comprehensive testing. The results demonstrate that the microservice-based system significantly improves the efficiency of managing employee attendance and leave, providing real-time monitoring and easier data management for BMKG. The study concludes that adopting microservices architecture in employee information systems can enhance scalability, flexibility, and maintainability, meeting the evolving needs of the organization